The Relationship Among Dietary Habit, Physical Fitness and Stress to the Obesity Condition of Indonesian National Police (Polri) Personnel - Putra, Novi Setyawan; Rahayu, Tandiyo; Yuwono, Cahyo (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2024)
Obesity is a physical condition that is of great concern to Polri Personnel. Apart from having an excessive anthropometric impact, it can also result in less optimal physical condition performance. This research aims to find out how big is the relationship: 1) between dietary habit and the obesity condition of Polri personnel, 2) between physical fitness and the obesity condition of Polri personnel, 3) between stress and the obesity condition of Polri personnel, and, 4) among dietary habit, physical fitness, and stress on the obesity condition of Polri personnel. This research is a type of correlational research. This research was conducted with subjects totaling 584 Polri personnel. Instruments used in the research were dietary habit instrument using the Food Frequency Questionnaires for Adults, physical fitness instrument using the National Police Physical Fitness Test, and stress instrument using the Police E-Mental Application. Data analysis techniques in the research involved product moment correlation test analysis, multiple correlation with the regression line equation, prerequisite test and hypothesis test as well as univariate and bivariate analysis. This research shows that: (1) there is a relationship between dietary habit and the obesity condition of Polri personnel with a p-value of 0,631 with significance value of 0,000, (2) there is a relationship between physical fitness and the obesity condition of Polri personnel with a p-value of 0,433 with significance value of 0,000, (3) there is a relationship between stress and the obesity condition of Polri personnel with a p-value of 0,429 with significance value of 0,000, (4) there is a relationship among dietary habit, physical fitness, and stress on the obesity condition of Polri personnel by obtaining an Fcount value of 13,143 and an Ftable value of 8,532 marked by an R value of 0,537 with a significance level of 0,000. Based on the research results above, it can be concluded that there is a fairly strong relationship among dietary habit, physical fitness, and stress on the obesity condition of Polri personnel, and it can be seen that dietary habit has the most significant influence compared to physical fitness and stress. Suggestion: Polri needs to adopt programs that encourage healthy dietary habit for the personnel, It is important for the Regional Police (Polda) physical fitness bureau to implement a comprehensive and sustainable physical fitness program, and for the Polda psychology bureau to provide programs or periodic checks that can help managing and reducing stress in the workplace.